The role of the IL-33/ST2 axis in autoimmune disorders: Friend or foe?. (December 2019) - Liu, Xiuxing; Xiao, Yichen; Pan, Yuan; Li, He; Zheng, Song Guo; Su, Wenru
Graphical abstract: Highlights: IL-33 and its receptors have convincing clinical value for autoimmune diseases. IL-33/ST2 axis mainly plays a detrimental role in a wide range of autoimmune diseases, although it has anti-autoimmune bioeffects. IL-33/ST2 axis promotes autoimmune diseases by regulating the balance between Th1/Th17 cells and Tregs. IL-33/ST2-mediated type 2 immune responses are equally important for the regulation of disease development. Abstract: Autoimmune diseases (ADs), which are common immune-mediated inflammatory syndromes, are characterized by an imbalance between T effector (Th)1/Th17 cells and T regulatory cells. Interleukin (IL)-33, a member of the IL-1 family, induces inflammatory disease development by mediating type 2 immune responses. Recently, IL-33/ST2 axis was reported to induce autoimmunity involving Th1 and Th17 cells. In this review, we focus on the expression, regulation and function of IL-33/ST2 pathway in the context of autoimmune disorders. We discuss the clinical potential of this signaling pathway in predicting disease activity and severity and offer possible future therapeutic alternatives.